Analysis of synoptic conditions for tornadic days over western Greece - Nastos, P. T.; Matsangouras, I. T. (Natural Hazards and Earth System Sciences, 2014)
Tornadoes have been reported in Greece during the last few decades and recent studies have given evidence that western Greece is an area vulnerable to tornadoes, waterspouts and funnel clouds In this study, the composite means and anomalies of synoptic conditions for tornadic events (tornadoes, waterspouts and funnel clouds) over western Greece are analyzed and discussed. The daily composite means of synoptic conditions were based on the National Centers for Environmental Prediction-National Center for Atmospheric Research (NCEP-NCAR) reanalysis data sets, for the period 12 August 1953 to 31 December 2012. The daily composite anomalies were calculated with respect to 30 years of climatological study (1981-2010) of the synoptic conditions. The analysis was carried out in terms of seasonal and monthly variability of composite means and anomalies of synoptic conditions for specific isobaric levels of 500, 700, 850, 925 hPa and the sea level pressure (SLP). In addition, an analysis and discussion about the dynamic lifted index from NCEP-NCAR reanalysis data sets is presented. The daily composite mean analysis of 500 hPa revealed a trough line across the northern Adriatic Sea and central Italy, associated with a SW upper-air stream over western Greece. The maximum composite anomalies were depicted at the isobaric level of 500 hPa during autumn, spring and summer, against winter when the anomaly appeared at 925 hPa isobaric level. In addition, 48% of tornado events during the autumn season occurred in pre-frontal weather conditions (cold fronts) and 27% developed after the passage of the cold front. Furthermore, the main difference in synoptic patterns between tornado and waterspout days along western Greece during the autumn season is the maximum daily composite anomaly over the Gulf of Taranto. © Author(s) 2014. CC Attribution 3.0 License.
Keywords: atmospheric dynamics; autumn; Climatology; cold front; Greece; Gulf of Taranto; Ionian Sea; Mediterranean Sea; sea level pressure; seasonal variation; Synoptic meteorology; temporal variation; tornado; waterspout